Comparison of Plain X-ray finding of Ventricular Enlargement with Echocardiography - Adhikary, KP; jha, S; Ghimire, RK; Pradhan, S (Nepalese Heart Journal, 2003)
Chest radiography is one of the first line investigations done to assess the cardiac size to rule out cardiomegaly. The present study was undertaken to compare the plain radiographic findings of ventricular enlargement with that of echocardiography.